Convergence theorems of subgradient extragradient algorithm for solving variational inequalities and a convex feasibility problem - Chidume, C. E.; Nnakwe, M. O. (Fixed point theory and algorithms for sciences and engineering, 2018)
Let C be a nonempty closed and convex subset of a uniformly smooth and 2-uniformly convex real Banach space E with dual space E ∗ . In this paper, a Krasnoselskii-type subgradient extragradient iterative algorithm is constructed and used to approximate a common element of solutions of variational inequality problems and fixed points of a countable family of relatively nonexpansive maps. The theorems proved are improvement of the results of Censor et al. (J. Optim. Theory Appl. 148:318–335, 2011 ).